PARTNERSHIP IN THE MANAGEMENT SYSTEM OF AN INSTITUTION OF HIGHER EDUCATION - Kharkivska, Alla; Prokopenko, Alona (Mountain School of Ukrainian Carpaty, 2023)
The article raises the problem of managing a higher education institution on a partnership basis, which allows organizing joint work between educational institutions, enterprises, scientific and public institutions, organizations and associations, administration and employees, teachers and students, stakeholders and practice bases. Research methods were used to achieve the goal: analysis; systematization and generalization; comparative analysis; forecasting internal and external partnership relations in the process of managing a higher education institution. Based on the analysis of scientific and pedagogical sources, the topic of research on partnership in institutions of higher education and partnership in management was investigated, the concept of "partnership" in institutions of higher education was clarified. The author tentatively distinguishes internal and external partnership in higher education institutions. It was found that the internal partnership in the management of the institution of higher education is implemented through the interaction between the management and subordinates. External partnership has a wider space of connections: with stakeholders and centers of practice, other institutions; with the administration of the city/region where the higher education institution is located, regional (territorial) education management bodies; with well-known theoreticians and practitioners in the field of management, education, science, etc.; with other institutions of higher education; with international organizations, institutions abroad, ensuring international cooperation of the institution of higher education. The partnership in the management of the institution of higher education is characterized, and the influence and motivation of such a relationship on the development of education and science in the country, the institution of higher education in general, individual professional growth of pedagogical and research-pedagogical workers, and the quality of education by students of higher education are clarified. The perspective of the research is defined as a detailed study of ways to implement external partnership in the management of a higher education institution at the state level.